EVALUASI DAN MANAJEMEN PENDIDIKAN BERBASIS AL-QUR’AN DAN HADITH - -, Sumarto (IAIN Kediri, 2016)
Generally, there are four management functions that are familiarized by community namely planning, organizing, directing, and controlling. In organizing function, there is staffing function. Leaders of organization are expected to be able to hold all management functions to get maximum management result. This article discusses evaluation and education management based on Al-QurÃ¢â‚¬â„¢an and hadith. Islamic education management is managing education based on the values of Islam as stated in al-QurÃ¢â‚¬â„¢an and hadith, and scholarsÃ¢â‚¬â„¢ thought. Besides, evaluation is one of Islamic education system components that must be conducted systematically and planned As a tool to measure the success or target that will be achieved in the process of Islamic education management.Ã‚Â Ã‚Â Ã‚Â Key words: education management, Evaluation, QurÃ¢â‚¬â„¢an and Hadith